Environmental Issue: peripheral dimension in a tourism policy? - Souza, Cynthia Oliveira de; Emmendoerfer, Magnus Luiz; Knupp, Marcos Eduardo Carvalho Gonçalves (Revista Turismo em Análise, 2017)
In the twentieth century, tourism was the object of attention in public policies of central governments in different countries. In the 21st century, due to the decentralization process, tourism has also become a sector of interest for subnational governments in favor of local and regional development. This article aims to analyze the environmental issue in the tourism policy planned by a subnational government in a federated state. For this, the documentary method was applied, whose collected data were compared in light of specialized literature. As a result, the priorities and issues considered important by government in a tourism policy were identified based on an analytical framework of 15 types of objectives and 22 forms of governmental action. In the analyzed situation, it was observed that the environmental issue is not something central in the current policy, which can cause concern for the sustainability of tourism beyond the economic dimension. Finally, the analytical framework employed makes it possible to understand the intentionality and comprehensiveness of a tourism policy.